2004
DOI: 10.1002/bjs.4510
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma showing thymic-like elements—a rare malignancy of the thyroid gland

Abstract: CASTLE with tumour-negative lymph nodes has a low risk of recurrence and surgery without adjuvant therapy is sufficient. Radiotherapy seems indicated when lymph nodes are tumour positive and can be effective for recurrent tumours. In selected patients surgery for recurrent tumour can improve quality of life and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 8 publications
1
65
0
1
Order By: Relevance
“…Besides thyroid, CASTLE also occurs in the left parapharyngeal space, 5 carotid and posterior space, 7 and subcutaneous tissue of head and neck. 8 This tumor occurs in middle-aged individuals with a mean age of 50 years and has a slight female predominance (female to male ratio, 1.3:1), 6,9 In our study, the mean age at initial diagnosis was 51 years, and the female to male ratio was 1:1.7. Because the number of cases was small, there seems to be no significant sexual predominance in our study.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Besides thyroid, CASTLE also occurs in the left parapharyngeal space, 5 carotid and posterior space, 7 and subcutaneous tissue of head and neck. 8 This tumor occurs in middle-aged individuals with a mean age of 50 years and has a slight female predominance (female to male ratio, 1.3:1), 6,9 In our study, the mean age at initial diagnosis was 51 years, and the female to male ratio was 1:1.7. Because the number of cases was small, there seems to be no significant sexual predominance in our study.…”
Section: Discussionmentioning
confidence: 44%
“…6,20 Some of the literature has reported that postoperative radiation could prevent locoregional recurrence. 1,5,9,21 In our study, 7 of 8 patients accepted postoperative radiation, and no locoregional recurrence occurred in 8 cases. For locoregional recurrence, Sun et al reported that recurrences may be controlled by salvage surgery with subsequent operation and/or radiotherapy.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…Chan and Rosai defined four clinic-pathologic entities: ectopic hamartomatous thymoma, ectopic cervical thymoma, spindle epithelial tumour with thymus-like differentiation (SETTLE), and Carcinoma showing thymic-like differentiation (CASTLE) [2]. This tumour is postulated to arise from either ectopic thymic tissue or remnants of branchial pouches, which retain the potential to differentiate along the thymic line [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, this disease has been designated as an independent clinicopathologic entity of thyroid tumors in the WHO classification [3]. A systematic review of English literature evidences less than thirty cases; from them, it clearly appears that CASTLE is considered an indolent slowgrowing neoplasia even when lymph nodes metastasis are present [4,5]. This data is confirmed in a recent study by the Japanese Society of Thyroid Surgery [5].…”
mentioning
confidence: 93%